Contemporary Deformation of the North China Plain From Global Positioning System Data. Issue 4 (26th February 2018) - Zhang, Y. G.; Zheng, W. J.; Wang, Y. J.; Zhang, D. L.; Tian, Y. T.; Wang, M.; Zhang, Z. Q.; Zhang, P. Z.
Abstract: The North China Plain (NCP) is a region with high level of seismic hazard. Previous Global Positioning System measurements, however, have shown a near absence of present‐day crustal deformation. Using updated Global Positioning System data covering three blocks of the eastern China, we discover that interseismic deformation in the NCP takes place in an ~1, 100 km wide left‐lateral shear zone of roughly east‐west orientation. The 6.0 ± 1.3 mm/yr interseismic left‐lateral shear over the NCP results in contemporary deformation that is eventually accommodated by earthquake ruptures of right‐lateral strike‐slip along the north‐northeast trending faults and anticlockwise block rotates. We suggest that rapid eastward motion of the rigid South China block, with respect to the rigid Amurian block, has created a left‐lateral shear couple to twist the nonrigid NCP to form the contemporary deformation. Key Points: North China Plain is a region with high‐level of earthquake hazard but absence of detectable crustal deformation Interseismic deformation of the NCP takes place in an ~1, 100 km wide left‐lateral shear zone of roughly east‐west orientation Permanent right‐lateral slips and block rotates on the NNE‐trending faults accommodate the left‐lateral transient shearing